ANALISIS PERTUMBUHAN PENERIMAAN PAJAK REKLAME PADA BADAN PENDAPATAN DAERAH KOTA MEDAN - Parlindungan Parlindungan (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2019)
This study aims to analyze the growth rate of advertisement tax revenue from 2014-to 2018 in the city of Medan. This research approach is descriptive. Data collection techniques are documentation and interviews. The data analysis technique used is descriptive. The results of this study indicate that the average growth rate of advertisement tax revenue for 2014-2017 reaches 15.11% with the criteria of Quite Successful. Advertising tax revenue in Medan City which has not reached the target that has been set is caused by the lack of awareness of taxpayers in fulfilling tax obligations and weak tax sanctions because the City of Medan has not enforced legal sanctions against negligent taxpayers